Effect of First Mother's Own Milk Feeding Time on the Risk of Moderate and Severe Bronchopulmonary Dysplasia in Infants With Very Low Birth Weight - Zhu, Yiming; Chen, Xiaohui; Zhu, Jingai; Jiang, Chengyao; Yu, Zhangbin; Su, Ailing (Frontiers in Pediatrics, 2022)
Objective: To explore the effect of mother's own milk (MOM) feeding time on the risk of moderate and severe bronchopulmonary dysplasia (BPD) in infants with very low birth weight (VLBW). Methods Clinical data from 630 infants with VLBW were retrospectively analyzed. Participants were divided into the early mother's own milk (EMOM) feeding group (first mother's own milk feeding time ≤72 h after birth, n = 397) and the late mother's own milk (LMOM) feeding group (first mother's own milk feeding time >72 h after birth, n = 233). Differences in the incidence of moderate and severe BPD among the two groups were analyzed using the chi-square test. Effects of MOM feeding time on the incidence of moderate and severe BPD were evaluated using univariate and multivariate logistic regression analysis. Results The incidences of moderate and severe BPD in the EMOM feeding group and the LMOM feeding group were 13.9% (55/397) and 21.0% (49/233), respectively (P = 0.019). Variate logistic regression analysis showed that the LMOM feeding group had an increased risk of moderate and severe BPD compared with the EMOM feeding group (OR = 1.656, 95% CI:1.083–2.532). The results of multivariate logistic regression analysis showed that the LMOM feeding group had an increased risk of moderate and severe BPD compared with the EMOM feeding group (OR = 1.894, 95% CI:1.127–3.185). Conclusion The first time of MOM feeding within 72 h after birth and the persistence of mother's own milk feeding during hospitalization can reduce the incidence of moderate and severe BPD in infants with VLBW.